The Effects of Using Micro Steel Fibre Towards Compressive Strength on Concrete Mix Design - SULAIMAN, MOHAMAD AFIQ IZZUDDIN; Ibrahim, Dafina Imani; Mohd Razif, Syaza NurBatrisyia; Mohammad Azmi, Mohamad Azim (Multidisciplinary Applied Research and Innovation, 2022)
Micro Steel fiber (MSF) concrete is one of the special concretes that normal concrete mix with discontinuous discrete steel fiber. The concrete will face several failures and considered as non-sustainable in the long term and need extra costs for maintenance and reconstruction. The study attempted to investigate the effect of using Micro Steel Fiber towards density and compressive strength development in concrete mix design. A widespread experimentation was performed to study the strength development of concrete containing Micro Steel Fibers. In present investigation series of cubes were casted with different percentage of volume of Micro Steel Fiber. Micro Steel Fiber are used at 0.5%, 0.75%, 1%, and 1.25%. Compression test were conducted on samples to measure the effect of Micro Steel Fiber on compressive strength of concrete. Samples were cure for 7 and 28 days before tested the strength using compression machine in Concrete Laboratory, UTHM Campus Pagoh. Data analysis was performed to determine how well Micro Steel Fiber concrete performs in terms of density and compressive strength. The highest result for compressive strength is 64.22 MPa produced by sample containing 1.25% of MSF. In the same way, the highest density also produced by the sample 1.25% of MSF at 28 days of curing period. In conclusion, the objective of this study are successfully achieved where adding Micro Steel Fiber in concrete sample increased the density and compressive strength development.